Escherichia coli Surface Characters of Ettawah Cross Breed Goats Milk on the Adhession Ability of Mammary Epithelial Cells - Lalita Prasiddhanti; A.E.T.H. Wahyuni (Jurnal Sain Veteriner, 2015)
Escherichia coli is a bacteria that may cause mastitis in goats. The ability of bacteria to infect is influenced by surface characters of each bacterial cell. Adhesion of bacteria on the udder epithelial cells plays an important role in the incidence of subclinical mastitis.The purpose of this study was to determine the surface characters of Escherichia coli colony morphology, such as the presence of polysaccharides capsule, hemagglutination activityand hydrophobicity contributes to the adhesion process. Three isolates of Escherichia coli isolated from Ettawah cross breed goats on Mandiri and Pangestu Farm at Turi, Sleman, Yogyakarta were used in the study. The ability of E. coli to fermentize lactose was done by examining its ability in fermented lactose on eosin methylene blue. Hemagglutination ability was seen by hemagglutination test using sheep erythrocytes at concentrations of 0.5%, 1%, 1.5% and 2%, respectively. Hydrophobicity expression was done by saltaggregation test using ammonium sulfate ([NH4] 2SO4) at concentrations of 1.2 M, 1.6 M, 2.0 M, 2.4 M and 3.2 M, respectively. The presence or absence of sera proteins was tested with sera soft agar, and the ability of adhesion was done by adhesion of Escherichia coli which has been marked by fluorescein isothiocyanate , with rats udder epithelial cells after birth. The results showed that isolates of E. coli with dry surface characters had athin polysaccharide capsule, positive hemagglutination , and hydrophobic, which had the ability to stick more on the udder epithelial cells after birth. Meanwhile, those with mucoid surface characters, had a thick polysaccharide capsule, negative hemagglutination, and hydrophilic which had a lower adhesion ability.